Quantitative investigation on the {10–12} twinning-detwinning behavior and twinning transfer of an extruded Mg-2.8Y sheet during compression-tension loading via quasi-in-situ EBSD observation - Tianjiao Li; Jiang Zheng; Manoj Gupta; Liuyong He; Lihong Xia; Bin Jiang (Journal of Materials Research and Technology, 2023)
Abundant {10–12} twins appeared in an extruded Mg-2.8Y (wt. %) sheet with rare-earth (RE) texture under compression along the transverse direction (TD). Twinning-detwinning behavior during compression-tension loading was quantitatively investigated via quasi-in-situ EBSD observation. The evolution of deformation mechanisms was quantitatively studied by calculation of the plastic strain fraction of twinning, detwinning, and dislocation slip. Twinning and detwinning were the dominant deformation modes in compression and reverse tension, respectively, owing to their relatively higher Schmid factors (SF) and lowest activation stresses (τ). Twin variants with SF ranking 1st and 2nd were activated preferentially while detwinning with low SF ranking showed high activation. The impact of texture and load path on variant selection was systematically discussed. Moreover, short twin chains only passing through two or three grains caused by twinning transfer were observed. Grain boundary misorientation angle (GBMA) and geometric compatibility factor (m’) were introduced to analyze the crystallographic characteristics of twinning transfer. GBMA ≤34.5° or m’ ≥ 0.80 is a necessary condition for most twinning transfer events. RE texture as well as the nearly uniform distribution of GBMA gave rise to short twin chains and restricted the formation of long twin bands. The relationship between GBMA and m’ was also discussed.